CertMike exam essentials CompTIA A+ core 1 exam 220-1101 - Chapple, Mike, 1975- (WILEY-SYBEX, 2022)
Skip the fluff and get straight to the essentials with an indispensable prep handbook for the CompTIA A+ Core 1 exam In CompTIA A+ CertMike: Prepare. Practice. Pass the Test! Get Certified! Core 1 Exam 220-1101, veteran tech experts and educators Mike Chapple and Mark Soper deliver a hands-on and practical roadmap to taking--and succeeding on--the CompTIA A+ Core 1 exam. You'll learn how to install, configure, and maintain computer equipment, mobile devices, and software for end users, service components based on customer requirements, understand networking basics, and apply essential cybersecurity methods. Ace the test using the proven CertMike approach: Prepare -- CertMike is your personal study coach, guiding you through all the exam objectives and helping you gain an understanding of how they apply to on-the-job tasks! Practice -- Each chapter includes two multiple choice practice questions. Work through the detailed explanations to evaluate each answer option and understand the reason for the best answer! Pass -- On exam day, use the critical knowledge you've learned when you're ready to take the test. You'll feel ready and confident to pass the exam and earn your certification! With a laser-focus on getting you job- and exam-ready, the book skips the fluff and gets right to the point of getting you familiar with IT basics and on the road to an in-demand IT certification and a new career in tech. You'll also get complimentary access to additional online study tools, complete with a bonus practice exam and audio recordings of the CertMike Exam Essentials. Banish test anxiety and feel ready to pass the test--the first time around! An indispensable resource for anyone preparing for their A+ certification, CompTIA A+ CertMike: Prepare. Practice. Pass the Test! Get Certified! Core 1 Exam 220-1101 is also a must-read for hardware and PC technicians seeking to upgrade their skillset.